ANALYSIS OF THE INFLUENCE OF ELECTRONIC WORD OF MOUTH (E-WOM), BRAND RESONANCE, AND BRAND TRUST ON PURCHASE DECISION AT TOKOPEDIA IN SINGKAWANG CITY - Sudarso, Erik (STKIP Singkawang, 2024)
This study investigates the influence of Electronic Word of Mouth (e-wom), Brand Resonance, and Brand Trust on Purchase Decisions within the context of Tokopedia, in Singkawang City. The electronic environment has transformed consumer behavior, emphasizing the need to understand the dynamics of online platforms. The research employs a descriptive quantitative approach, utilizing questionnaires to collect data from Tokopedia users in Singkawang City up to 100 respondents. The research results show that electronic word of mouth, brand resonance, and brand trust have a positive significant impact on purchase decision at Tokopedia in Singkawang City. The findings aim to provide valuable insights for e-commerce practitioners and marketers, enhancing their understanding of the factors influencing consumer choices in the digital marketplace. This research contributes to the growing body of literature on e-commerce and consumer behavior, offering practical implications for businesses operating in the competitive online landscape.